The Basic Concept of Myers-Briggs Type Indicator to Determine Student Personality - Mentari, Akmalia Siwi Mentari; Eliasa, Eva Imania (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This research aims to discuss the understanding of the Myers-Briggs Type Indicator test to determine student personality. The method in this research is a theoretical or conceptual study using a qualitative descriptive method through a literature study approach or library research, which is a method of collecting data by understanding and studying theories from various literatures related to the research. The results of the study show that the Myers-Briggs Type Indicator has great potential to be applied to guidance and counseling services. The development of Jung's typology from Myers & Briggs formed 16 personality types. Each individual has all four components of the personality. The four components of personality form a certain personality type. The combination of several basic processes forms an individual's character. Individuals have two basic attitudes, viz: extrovert and introvert. These two attitudes are based on four separate functions. These functions are thinking, feeling, sensing, and intuition. Knowledge of these personality types is an important component for an educator to understand student characteristics. Based on this understanding, educators can understand that differences are natural, educators can also identify strengths and things that can be developed by students and can motivate them based on their personality characteristics.